E-Learning in Kazakhstan: Stages of Formation and Prospects for Development - Sapargaliyev, Daniyar (International Journal of Advanced Corporate Learning (iJAC), 2012)
Today Kazakhstan is a country with a very high level of literacy. The living standards and economy in the country are growing very rapidly. But the emergence of e-Learning was held stable and haphazard. This is due to many factors - later involvement in the process of societyâ??s â??informatizationâ?, lack of attention to the development of distance and corporate learning. Meanwhile, e-Learning is important and a priority in education and business sectors. The Government is taking all efforts to diversify the process of implementing e-Learning for all citizens. The population of Kazakhstan is in a huge need for digital literacy. Year by year an increasing number of citizens are wishing to develop their â??digitalâ? culture. Many Kazakhs are ready to acquire new knowledge through e-Learning at universities and in the workplaces. In this paper we will consider the formation of e-Learning in Kazakhstan and contemporary challenges for the further development of e-Learning.